Economic impacts of soil fertility management research in West Africa - Akinola, Adebayo A.; Alene, Arega D.; Adeyemo, R.; Sanogo, D.; Olanrewaju, A.S. (2009)
This paper assesses the potential economic impacts of balanced nutrient management systemstechnology options: BNMS-manure, which combines inorganic fertilizer and organic manure,and BNMS-rotation, which is maize–soybean rotation, in maize-based systems in the northernGuinea savanna areas of Nigeria, Ghana, Togo and Benin. The economic surplus analysissuggested that BNMS-manure research and extension could achieve returns ranging from 17 to25% and a maximum adoption of 24 to 48%, for the conservative and base scenario respectively;and that BNMS-rotation research and extension could achieve returns ranging from 35 to 43%and a maximum adoption of 20 to 40%, for the conservative and base scenario respectively. Ourresults were consistent with earlier economic analyses which showed that BNMS-rotation wasmore productive, profitable and acceptable to farmers than BNMS-manure. It may be difficult toachieve large-scale adoption of BNMS-manure because the increases in yields are smaller andmarkets for manure are missing.